A new synthesis of inosine from 5-amino-1-beta-D-ribofuranosyl-4-imidazole-carboxamide. - Okutsu, M (1976)
Inosine was prepared (15% yield) by treatment of 5-amino-1-beta-D-ribofuranosyl-4-imidazolecarboxamide (AICA-riboside) with chloroform in the presence of sodium methoxide. This ring closure can be reasonably explained by assuming the formation of dichlorocarbene from chloroform and alkali. Carbon tetrachloride or hexachloroethane as a carbene source was more effective for the ring closure of AICA-riboside, giving inosine in 48% and 51% yields respectively.